Delivery Route Management based on Dijkstra Algorithm - Ng Lih Sheng; Nureize Arbaiy; Chuah Chai Wen Wen; Pei-Chun Lin (مجلة بغداد للعلوم)
For businesses that provide delivery services, the efficiency of the delivery process in terms of punctuality is very important. In addition to increasing customer trust, efficient route management, and selection are required to reduce vehicle fuel costs and expedite delivery. Some small and medium businesses still use conventional methods to manage delivery routes. Decisions to manage delivery schedules and routes do not use any specific methods to expedite the delivery settlement process. This process is inefficient, takes a long time, increases costs and is prone to errors. Therefore, the Dijkstra algorithm has been used to improve the delivery management process. A delivery management system was developed to help managers and drivers schedule efficient ways to deliver product orders to recipients. Based on testing, the Dijkstra algorithm that has been included in the nearest route search function for the delivery process has worked well. This system is expected to improve the efficient management and delivery of orders.